ESP32-Based Smart Gloves for Message Transmission via Hand Gestures Using Telegram Application - Ferdiyanto, Rania Zakia; Bayu Aji Laresa; Farraz Abdi Farein (Indonesian Journal of Electrical Engineering and Electronics, 2024)
This research aims to develop an ESP32-based Smart Gloves system that facilitates message transmission via hand gestures, integrating Telegram as a communication platform. The system utilizes an MPU9250 motion sensor embedded in the glove to detect hand gesture patterns, which are then processed by the ESP32 microcontroller to convert these gestures into text messages. The translated messages are sent in real-time through the Telegram application to the intended recipient. This process offers a solution for users with verbal communication limitations, such as stroke patients, enabling them to communicate easily and effectively. Testing results demonstrate that the system can accurately convert hand gestures into text messages and transmit them via Telegram promptly.